Two near-inertial peaks in antiphase controlled by stratification and tides in the Yellow Sea - Hu, Yibo; Yu, Fei; Chen, Zifei; Si, Guangcheng; Liu, Xingchuan; Nan, Feng; Ren, Qiang (Frontiers in Marine Science, 2023)
The Yellow Sea is a strongly tidally-driven and highly stratified shallow sea due to the presence of the Yellow Sea Cold Water Masses. Observations show that the near-inertial event sustains for 10 days with a peak near-inertial velocity of 0.15m/s, which accounts for 30% of the total velocity during the passage of a cyclone. Near-inertial velocity is dominated by the first baroclinic mode with one zero-crossing at the depth of the maximum stratification and two velocity peaks in the mixed layer and below the thermocline, respectively. Combined with numerical simulation analysis, it was found that the two velocity peaks are controlled by stratification and tides. In the mixed layer, the near-inertial peak is induced by wind stress, but the strong stratification constrains the downward propagation of the near-inertial energy. With respect to the near-inertial peak below the thermocline, it is associated with a barotropic wave generated at the coast and propagating offshore. However, the near-inertial flow within the bottom layer is reduced by the eddy viscosity of the tidal currents. Within the thermocline, the pronounced vertical convection due to velocity shear weakens the intensity of the near-inertial flow.